An open-treatment six-week study of the clinical effectiveness of Paliperidone Palmitate in schizophrenia: data from acute units in Spain (SHADOW study). (3rd July 2018) - Parellada, Eduard; Bioque, Miquel; Serrano, Manuel; Herrera, Berta; García Dorado, Marta; ,
Abstract: Objectives: To evaluate clinical evolution of patients with schizophrenia admitted in acute units because of a relapse and treated with once-monthly Paliperidone Palmitate (PP1M). Methods: This multicentre, open-label, prospective observational study followed patients with schizophrenia treated with PP1M in acute psychiatric units for up to 6 weeks. Results: Out of the 280 enrolled patients, 61 received PP1M as antipsychotic monotherapy, and 219 in combination with other antipsychotics. The average Clinical Global Impression–Schizophrenia (CGI-SCH) score decreased from 4.7 at baseline to 3.3 at final visit ( p  < .0001); the change was clinically and statistically significant both in patients treated with PP1M in monotherapy and in combination with other antipsychotics. Clear improvements in functioning and high patient satisfaction with the treatment were observed. Time from admission to PP1M therapy initiation correlated with the length of hospital stay ( p  < .0001); earlier start of PP1M treatment was associated with shorter hospital stay. Adverse events were reported in 7.1% of patients (all non-serious). Conclusions: PP1M was effective and well tolerated in treatment of acute episodes of schizophrenia both in monotherapy and in combination with other antipsychotics in clinical setting. Early start of PP1M therapy in acute schizophrenia episodes might help to shorten hospital stay.